More lessons learned: Future research in talent identification and development - Baker, J.; Cobley, S.; Schorer, J. (Talent identification and development in sport. International perspectives, 2021)
As in our first edition of this text, the chapters presented herein contain a wealth of information on the theoretical underpinnings of talent science (Part 1) and leading examples of best practices from around the globe (Part 2). Undoubtedly, there has been considerable scholarship and research since 2012. However, as the populär astrophysicist Neil Degrass Tyson noted (2019) 'as the area of our knowledge grows, so too does the perimeter of our ignorance'. Thus, our intent in this chapter is to update our discussion from the last edition and highlight 'the perimeter of our ignorance', illuminating future directions for researchers and practitioners. In our first edition, we noted there was comparatively little research focusing on talent identification/selection (e.g., predictors of selection, evaluations of selection decisions, etc.) compared to research on athlete development (e.g., factors affecting the processes of skill acquisition and development). Since 2012, there has been considerably more work on Identification and selection, particularly work focusing on predictors of selection using cross-sectional and longitudinal designs (Cobley & Till, 2017). This work highlights the importance of understanding the factors affecting how talent identification and selection occurs, as well as the reliability and validity of these decisions (cf. Chapters 4 and 8). That said, much of this work has been unidimensional (e.g., examining physiological variables only), which is undoubtedly inadequate for capturing the complete profile of variables involved in identification and selection decisions (Johnston, Wattie, Schorer, & Baker, 2017).